SO021EFFECTS OF SODIUM-GLUCOSE COTRANSPORTER 2 INHIBITOR, CANAGLIFLOZIN ON GLOMERULAR HYPERFILTRATION AND OXIDATIVE STRESS IN MICE WITH TYPE 2 DIABETES. (6th June 2020) - Kondo, Megumi; KIDOKORO, KENGO; Wada, Yoshihisa; Tokuyama, Atsuyuki; Kadoya, Hiroyuki; Sasaki, Tamaki; Kashihara, Naoki
Abstract: Background and Aims: In most developed countries, diabetic kidney disease (DKD) is the most common cause of chronic kidney disease, which can lead to end-stage renal disease. In recent clinical trials, sodium–glucose cotransporter 2 inhibitors (SGLT2is) slowed the progression of kidney disease as compared with a placebo in patients with type 2 diabetes. One of the main mechanisms of the renoprotective effects of SCLT2is in DKD is considered the ability of these inhibitors to improve glomerular hyperfiltration. We previously demonstrated that the adenosine/adenosine A1 receptor pathway played a pivotal role in the tubuloglomerular feedback(TGF) system in a type 1 diabetic model, Akita mice ( Circulation, 2019). We also reported that increased oxidative stress was involved in the pathogenesis of diabetic vascular complications. Uncoupling of endothelial nitric oxide (NO) synthase (eNOS) via oxidation of tetrahydrobiopterin (BH4), a cofactor required for NO production, played a major role in generation of oxidative stress ( AJPRP, 2005; JASN, 2013). In the present study, we explored the renal protective effects of SGLT2 inhibition, with a focus on glomerular hemodynamics and glomerular oxidative stress. Method: This study used type 2 diabetic db/db mice and db/m+ mice as a control (male, 8wk old). We developed a novel method to measure the glomerular filtration rate of single nephrons (SNGFRs) in mice using multiphoton laser microscopy. In the first experiment, we measured the SNGFRs in 12 wk-old db/db and db/m+ mice to confirm glomerular hyperfiltration. Next, we evaluated the SNGFRs change before and after the administration of a single dose of canagliflozin (CANA) (10 mg/kg). The SNGFRs, glomerular permeability of macromolecules, glomerular reactive oxygen species (ROS) and NO production, and tetrahydrobiopterin (BH4) level in serum and kidney were evaluated after the CANA treatment for 8 wk. Finally, human glomerular endothelial cells (hGECs) were exposed to normal glucose (5 mmol/L), high glucose (30 mmol/L of D-glucose), or a hyperosmotic control (5 mmol/L of D-glucose plus 25 mmol/L of L-glucose) in the presence or absence of CANA (10 μmol/L). Results: The CANA treatment ameliorated glomerular hyperfiltration in the db/db mice. In the db/db mice, glomerulus ROS production increased, and NO production decreased as compared with the levels in the control mice. CANA improved the imbalance between ROS and NO production. The serum and kidney concentrations of BH4 declined in the non-treated db/db mice, whereas the CANA treatment preserved the BH4 level. Leakage of 70-kD FITC-labeled albumin into the urinary space was observed in the db/db mice. The CANA treatment reduced the amount of FITC-labeled albumin in the urinary space of the db/db mice. The CANA treatment also alleviated vascular endothelial damage in glomeruli. BH4 levels decreased in the hGECs exposed to high glucose. CANA did not improved BH4 level in the hGECs exposed to high glucose. Conclusion: SGLT2i ameliorated glomerular hyperfiltration, preserving BH4 levels and improving the glomerular ROS/NO imbalance in type 2 diabetic mice.